2017
DOI: 10.1093/ecco-jcc/jjx165
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Histological Remission in Ulcerative Colitis: Discrepancies Between Daily Practice and Expert Opinion

Abstract: Current UC histological scores reliably assess limited histological inflammation in UC patients. The discrepancy between the initial histological assessment and the reassessment by dedicated GI pathologists suggests a gap between daily practice and academic expertise. This issue may limit the implementation of HR as a treatment target for UC in daily practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 45 publications
(49 reference statements)
0
21
0
Order By: Relevance
“…Comparative trials revealed a strong correlation between Geboes score, Nancy index and Robarts score suggesting that the available validated scores may provide overlapping data. Instead, a study by Römkens et al showed that the correlation between the nonvalidated scores and between the nonvalidated and validated scores was moderate, highlighting how the histologic score can influence patient management and therapeutic decisions. Dosage of FC levels was performed through different methods and the most commonly adopted test was ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative trials revealed a strong correlation between Geboes score, Nancy index and Robarts score suggesting that the available validated scores may provide overlapping data. Instead, a study by Römkens et al showed that the correlation between the nonvalidated scores and between the nonvalidated and validated scores was moderate, highlighting how the histologic score can influence patient management and therapeutic decisions. Dosage of FC levels was performed through different methods and the most commonly adopted test was ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…To maximally decrease the variability in the histological scoring, we recommend extensive training and the application of scoring conventions in clinical practice for those histopathologists that use the incorporate histological scoring for UC. 5,24 Finally, our study might have implications for the development of new endoscopic tools.…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“… 5 Additionally, one of the main clinical aims in UC treatment is continuous maintenance of mucosal healing in patients with UC. 6 Nowadays, mucosal healing can be maintained for 12 months with continued application of immunosuppressive drugs and biological agents, but aggravation of colon inflammation is inevitable when treatment stops. 3 Accordingly, new noninvasive markers and therapeutic approaches for monitoring and maintaining mucosal healing in patients with UC should be defined.…”
Section: Introductionmentioning
confidence: 99%